P46 THREE–DIMENSIONAL ECHOCARDIOGRAPHY EVALUATION OF MITRAL VALVE ANATOMY AFTER PERCUTANEOUS EDGE TO EDGE REPAIR. (18th May 2022) - Polizzi, V; Chianta, V; Russo, M; Ranocchi, F; Cammardella, A; Pergolini, A; Manzara, C; Musumeci, F
Abstract: Background: Transcatheter edge–to–edge repair (TEER) is a safe strategy for high–risk patients with significant mitral regurgitation (MR). We aimed to characterize by three–dimensional echocardiography (3D–E) acute reshaping of mitral valve apparatus, with specific reference to the underlying MR mechanism (functional (FMR)and degenerative (DMR)) Methods: We prospectively enrolled 15 patients(November 2020 to September 2021), (median age 81 y.o, range 79–84, 50% male, 1 urgent procedure) with severe mitral valve regurgitation who underwent intra–procedural 3D–E before and after device deployment. Using a dedicated semiautomatic software, we obtain parametric quantification of mitral valve anatomy to describe acute changes in FMR and DMR. Results: Eight patients (53%) were affected by FMR of whom one case was performed as bridge to heart transplantation candidacy. In the remaining 7 DMR cases, P2 prolapse was present in 5 (71%), commissural flail and A2 flail in 2 cases. Procedural success (MR < 2) was achieved in 14 cases (93%). 30–day survival was 100% in elective cases. A second clip was necessary in 8 patients (53%). After TEER, the FMR group experienced an immediate annular reshaping, with reduction of antero–posterior diameter (p 0.05), next to a recovery of physiological saddle–shape, defined by lower non–planar angle (p = 0.001) and higher annulus height (p ≤ 0.001). The DMR group showed a trend of decrease of maximum annular velocity, addressing a stabilizing effect of the device.The deployment of a second clip has no significant effect of the annular reshaping in both groups. Conclusions: TEER causes multiple effects on mitral valve geometry which variesaccording to MR mechanism. Three–D parametric quantification of MV anatomy identifiedspecific parameters of acute annular remodeling. FMR exhibited pronounced modification. This "annuloplasty–like" effect may play a role in the late freedom from MR.